Heffernan v. City of Paterson (2016): A New Element in Constitutional Tort Law—It's Not Necessarily What the Public Employer Did, but What It Intended to Do That Counts. (September 2019) - Rosenbloom, David H.
Heffernan v. City of Paterson, Mayor Jose Torres, Police Chief James Wittig, and Police Director Michael Walker modified and expanded constitutional tort law by (a) authorizing suits against public officials, employees, and municipalities for unconstitutionally retaliating against personnel on the mistaken belief that they engaged in constitutionally protected speech and (b) allowing such suits to proceed even when those personnel deny having exercised First Amendment rights. Heffernan also affords procedural protection to public employees disciplined for what was incorrectly considered protected speech. The implications for public personnel administration are (a) potentially greater difficulty for personnelists and managers to receive qualified immunity in summary judgments, (b) potential liability for a new type of constitutional tort with uncertain boundaries, and (c) and, unexpectedly, judicial intrusion into personnel administration by judges' second-guessing the reasonableness of managerial actions based on erroneous assessments of the constitutionality of employees' speech. Consequently, public personnelists and managers should closely follow Heffernan's progeny to protect rights and avoid suits.